Lambert‐Eaton myasthenic syndrome with anti‐acetylcholine receptor antibody and anterior mediastinal tumor. (13th April 2017) - Matsumoto, Hideyuki; Ohtomo, Gaku; Akahori, Tsugumi; Hashida, Hideji
Abstract: This report describes the case of a 65‐year‐old male who complained of muscular weakness of the legs with easy fatigability. Blood and imaging examinations showed positive anti‐acetylcholine receptor antibody and an anterior mediastinal tumor (probably a thymic cyst), suggesting the diagnosis of myasthenia gravis (MG). However, neurological and electrophysiological examinations suggested the diagnosis of Lambert‐Eaton myasthenic syndrome (LEMS). We searched repeatedly for malignant tumors. Small cell lung cancer (SCLC) was found. Chemotherapy reduced the SCLC and improved the patient's clinical symptoms. On the basis of an accurate diagnosis of LEMS, we were able to detect SCLC and administer chemotherapy at an early stage. Anti‐P/Q‐type voltage‐gated calcium channel antibody was negative. In our case, MG and LEMS overlap syndrome in addition to MG should be differentiated. For the differentiation, the strict electrophysiological criteria of LEMS were useful.